Rating of Perceived Exertion as a Method of Volume Autoregulation Within a Periodized Program. Issue 6 (June 2018) - Helms, Eric R.; Cross, Matt R.; Brown, Scott R.; Storey, Adam; Cronin, John; Zourdos, Michael C.
Abstract : Abstract: Helms, ER, Cross, MR, Brown, SR, Storey, A, Cronin, J, and Zourdos, MC. Rating of perceived exertion as a method of volume autoregulation within a periodized program. J Strength Cond Res 32(6): 1627–1636, 2018—The purpose of this investigation was to observe how a rating of perceived exertion (RPE)-based autoregulation strategy impacted volume performed by powerlifters. Twelve (26 ± 7 years, n = 9 men, n = 3 women) nationally qualified powerlifters performed the back squat, bench press, and deadlift 3x per week on nonconsecutive days in a session order of hypertrophy, power, and then strength; for 3 weeks. Each session subjects performed an initial top set for a prescribed number of repetitions at a target RPE. A second top set was performed if the RPE score was too low, then subsequent back-off sets at a reduced load were performed for the same number of repetitions. When the prescribed RPE was reached or exceeded, sets stopped; known as an "RPE stop." The percentage load reduction for back-off sets changed weekly: there were 2, 4, or 6% RPE stop reductions from the top set. The order in which RPE stop weeks were performed was counterbalanced among subjects. Weekly combined relative volume load (squat + bench press + deadlift), expressed as sets x repetitions x percentage 1-repetition maximum was different between weeks ( p < 0.001): 2% = 74.6 ± 22.3; 4% = 88.4 ± 23.8; 6% = 114.4 ± 33.4. Combined weekly bench press volume (hypertrophy + power + strength) was significantly higher in accordance with load reduction magnitude (2% > 4% > 6%; p ⩽ 0.05), combined squat volume was greater in 6 vs. 2% ( p ⩽ 0.05), and combined deadlift volume was greater in 6 vs. 2% and 4% ( p ⩽ 0.05). Therefore, it does seem that volume can be effectively autoregulated using RPE stops as a method to dictate number of sets performed.